2021
DOI: 10.1007/s00109-021-02080-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis is linked to MAPKERK overactivity in microglia

Abstract: Reassessment of published observations in patients with multiple sclerosis (MS) suggests a microglial malfunction due to inappropriate (over)activity of the mitogen-activated protein kinase pathway ERK (MAPKERK). These observations regard biochemistry as well as epigenetics, and all indicate involvement of this pathway. Recent preclinical research on neurodegeneration already pointed towards a role of MAPK pathways, in particular MAPKERK. This is important as microglia with overactive MAPK have been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 96 publications
2
24
0
1
Order By: Relevance
“…MS also precedes autoimmune attack, and therefore AS of MAP2K4 in active lesions detected with NEASE may represent dysregulated immune responses originating from the infiltrating immune cells or inflammatory-activated brain cells. This is supported by previous studies that found (i) overactivity of MAPK pathways in microglia (the resident immune cell of the brain) during neurodegeneration [78,79], and (ii) increased phosphorylation of MAPK kinases in the systemic immune cells of MS patients [80,81]. A recent study also characterized activated MS-specific pathways in immune cells from blood using phosphoproteomics.…”
Section: Nease Characterizes Complex Disorders Such As Multiple Sclerosissupporting
confidence: 79%
See 1 more Smart Citation
“…MS also precedes autoimmune attack, and therefore AS of MAP2K4 in active lesions detected with NEASE may represent dysregulated immune responses originating from the infiltrating immune cells or inflammatory-activated brain cells. This is supported by previous studies that found (i) overactivity of MAPK pathways in microglia (the resident immune cell of the brain) during neurodegeneration [78,79], and (ii) increased phosphorylation of MAPK kinases in the systemic immune cells of MS patients [80,81]. A recent study also characterized activated MS-specific pathways in immune cells from blood using phosphoproteomics.…”
Section: Nease Characterizes Complex Disorders Such As Multiple Sclerosissupporting
confidence: 79%
“…Novel developments in genome-editing tools and gene-specific strategies have made it possible to use antisense oligonucleotides or small modulators for splice modification. This is already used in the rare neuromuscular disease, spinal muscular atrophy, where an antisense oligonucleotide binds to a site near splicing to ensure the inclusion of an exon during the splicing event [78].…”
Section: Nease Characterizes Complex Disorders Such As Multiple Sclerosismentioning
confidence: 99%
“…While p38 is mainly involved in neuronal apoptosis and mobilizing major SCI-related proinflammatory cytokines, ERK1/2 is implicated in multiple aspects of CNS injury pathophysiology. It has been described that ERK overactivity in microglia imposes a detrimental effect on adjacent OLs by inducing proinflammatory mediators such as IL-1β, IL-6, and TNF-α, leading to demyelination [56]. Therefore, inhibition of the ERK pathway has been shown to promote OL generation and recovery from demyelinating diseases [23].…”
Section: Discussionmentioning
confidence: 99%
“…This also holds for the putative inflammatory role(s) of EBV-derived components (EBERs in exosomes and/or EBNA1-DNA complexes) in triggering locoregional activation of the MS-characteristic inflammatory MAPK pathway in microglia (2,9). The role and mechanism of EBV and cytokines on activating other endogenous viruses, such as HERVs and HHV-6 also deserves attention (9). Since all MS patients are EBNA-1-IgG positive, the involvement of EBNA-1-IgG immune complex formation and inflammation near CNS should be further analysed.…”
Section: Future Studies On the Relationship Between Ebv And Msmentioning
confidence: 98%
“…Defining the roles of autoimmune responses as cause or consequence in the pathogenesis of MS and their potential link to viral antigen mimicry and auto-reactive EBV-infected B-cells merits further analysis. This also holds for the putative inflammatory role(s) of EBV-derived components (EBERs in exosomes and/or EBNA1-DNA complexes) in triggering locoregional activation of the MS-characteristic inflammatory MAPK pathway in microglia (2,9). The role and mechanism of EBV and cytokines on activating other endogenous viruses, such as HERVs and HHV-6 also deserves attention (9).…”
Section: Future Studies On the Relationship Between Ebv And Msmentioning
confidence: 99%